Effect of lorcaserin on prevention and remission of type 2 diabetes in overweight and obese patients (CAMELLIA-TIMI 61): a randomised, placebo-controlled trial. Issue 10161 (24th November 2018) - Bohula, Erin A; Scirica, Benjamin M; Inzucchi, Silvio E; McGuire, Darren K; Keech, Anthony C; Smith, Steven R; Kanevsky, Estella; Murphy, Sabina A; Leiter, Lawrence A; Dwyer, Jamie P; Corbalan, Ramon; Hamm, Christian; et al.
Summary: Background: There is a direct relationship between bodyweight and risk of diabetes. Lorcaserin, a selective serotonin 2C receptor agonist that suppresses appetite, has been shown to facilitate sustained weight loss in obese or overweight patients. We aimed to evaluate the long-term effects of lorcaserin on diabetes prevention and remission. Methods: In this randomised, double-blind, placebo-controlled trial done in eight countries, we recruited overweight or obese patients (body-mass index ≥27 kg/m 2 ) with or at high risk for atherosclerotic vascular disease. Eligible patients were aged 40 years or older; patients at high risk for atherosclerotic vascular disease had to be aged 50 years or older with diabetes and at least one other risk factor. Patients were randomly assigned to receive either lorcaserin (10 mg twice daily) or matching placebo. Additionally, all patients had access to a standardised weight management programme based on lifestyle modification. The prespecified primary metabolic efficacy endpoint of time to incident diabetes was assessed in patients with prediabetes at baseline. The prespecified secondary outcomes for efficacy were incident diabetes in all patients without diabetes, achievement of normoglycaemia in patients with prediabetes, and change in glycated haemoglobin (HbA1c ) in patients with diabetes. Hypoglycaemia was a prespecified safety outcome. Analysis was by intention to treat, using Cox proportional hazard models for time-to-event analyses. This trial is registered withClinicalTrials.gov, numberNCT02019264 . Findings: Between Feb 7, 2014, and Nov 20, 2015, 12 000 patients were randomly assigned to lorcaserin or placebo (6000 patients in each group) and followed up for a median of 3·3 years (IQR 3·0–3·5). At baseline, 6816 patients (56·8%) had diabetes, 3991 (33·3%) prediabetes, and 1193 (9·9%) normoglycaemia. At 1 year, patients treated with lorcaserin had a net weight loss beyond placebo of 2·6 kg (95% CI 2·3–2·9) for those with diabetes, 2·8 kg (2·5–3·2) for those with prediabetes, and 3·3 kg (2·6–4·0) for those with normoglycaemia (p<0·0001 for all analyses). Lorcaserin reduced the risk of incident diabetes by 19% in patients with prediabetes (172 [8·5%] of 2015 vs 204 [10·3%] of 1976; hazard ratio 0·81, 95% CI 0·66–0·99; p=0·038) and by 23% in patients without diabetes (174 [6·7%] of 2615 vs 215 [8·4%] of 2569; 0·77, 0·63–0·94; p=0·012). Lorcaserin resulted in a non-significant increase in the rate of achievement of normoglycaemia in patients with prediabetes (185 [9·2%] vs 151 [7·6%]; 1·20, 0·97–1·49; p=0·093). In patients with diabetes, lorcaserin resulted in a reduction of 0·33% (95% CI 0·29–0·38; p<0·0001) in HbA1c compared with placebo at 1 year from a mean baseline of 53 mmol/mol (7·0%). In patients with diabetes at baseline, severe hypoglycaemia with serious complications was rare, but more common with lorcaserin (12 [0·4%] vs four [0·1%] events; p=0·054). Interpretation: Lorcaserin decreases risk for incident diabetes, induces remission of hyperglycaemia, and reduces the risk of microvascular complications in obese and overweight patients, supporting the role of lorcaserin as an adjunct to lifestyle modification for chronic management of weight and metabolic health. Funding: Eisai.